2008
DOI: 10.1007/s12072-008-9109-7
|View full text |Cite
|
Sign up to set email alerts
|

Cirrhotic cardiomyopathy

Abstract: Cirrhotic cardiomyopathy is a recently recognized condition in cirrhosis consisting of systolic incompetence under condition of stress, diastolic dysfunction related to altered diastolic relaxation, and electrophysiological abnormalities in the absence of any known cardiac disease. It can be diagnosed by using a combination of electrocardiograph, 2-dimensional echocardiography, and various serum markers such as brain natriuretic factor. The underlying pathogenetic mechanisms include abnormalities in the b-adre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
124
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 173 publications
(129 citation statements)
references
References 95 publications
3
124
0
2
Order By: Relevance
“…A number of studies have reported electrophysiological abnormalities as common findings of cardiac dysfunction in liver cirrhosis. Electrocardiographic abnormalities are an early manifestation of cardiac changes in patients with liver disease: a prolongation of the QT interval, which is the hallmark of the ECG alterations could be related to severity of liver disease [83,84]. Worsening of cardiac function after OLT, however, is brief and resolves within about 6 months, when the hyperdynamic circulation disappears.…”
Section: Cirrhotic Cardiomyopathymentioning
confidence: 99%
“…A number of studies have reported electrophysiological abnormalities as common findings of cardiac dysfunction in liver cirrhosis. Electrocardiographic abnormalities are an early manifestation of cardiac changes in patients with liver disease: a prolongation of the QT interval, which is the hallmark of the ECG alterations could be related to severity of liver disease [83,84]. Worsening of cardiac function after OLT, however, is brief and resolves within about 6 months, when the hyperdynamic circulation disappears.…”
Section: Cirrhotic Cardiomyopathymentioning
confidence: 99%
“…The pathophysiological background of the diastolic dysfunction in cirrhosis is the increased stiffness of the myocardial wall, which is often caused by myocardial hypertrophy and fibrosis due to activation of the RAAS [29]. Subendothelial edema and increased interstitial collagen deposition play a further role in the decreased ability for relaxation [2,8]. Based on the severity of diastolic heart function, patients may be relatively asymptomatic.…”
Section: Diastolic Functionmentioning
confidence: 99%
“…The functional and structural changes of the myocardium have been referred as cirrhotic cardiomyopathy (CCM), a slow progression myocardial dysfunction associated with cirrhosis [1]. Most importantly, this condition should not be confused with alcoholic cardiomyopathy where the underlying mechanism responsible for the structural and functional cardiac abnormalities is well defined [2]. In contrast to alcoholic cardiac disease, in the case of CCM any well-defined underlying provoking factor(s) can be identified; however, sometimes iron overload or alcohol consumption may worsen the already hampered structural and functional condition of the myocardium [3].…”
Section: Introductionmentioning
confidence: 99%
“…Cirrhotic cardiomyopathy develops in about half of all cirrhotic patients and markedly affects the long-term morbidity and mortality of those patients [1][2][3]. Cirrhotic cardiomyopathy results from multifactorial organic myocardial changes and is defined as systolic and diastolic cardiac dysfunction with co-existing electrocardiographic (ECG) abnormalities or abnormal serologic markers (brain natriuretic peptide [BNP], troponin 1, adrenomedullin) in patients with cirrhosis in the absence of cardiac diseases [1,2,4]. Patients with decompensated cirrhosis have been demonstrated to have elevated levels of the N-terminal prohormone of brain natriuretic peptide (NT-proBNP) and left ventricle (LV) diastolic dysfunction [5].…”
mentioning
confidence: 99%